Pregabalin Toxicity Manifesting as Reversible Encephalopathy With Continuous Triphasic Waves in Electroencephalogram. Issue 5 (September 2017) - Parekh, Mihir; Dash, Gopal Krishna; Ahamed, Isthiaque
Abstract : Abstract: A 74-year-old man with peripheral neuropathy due to diabetes presented with deliberate ingestion of 450 mg of pregabalin (PBG) over a period of 8 hours followed by altered mental status. A bedside electroencephalogram was performed to rule out nonconvulsive status epilepticus, which showed continuous triphasic waves (TWs) with slow background activity. He recovered after 48 hours of stopping PBG, and his repeat electroencephalogram after 72 hours did not show any TWs. We present a rare case of PBG-induced TWs thereby highlighting the extent of the etiologic spectrum of TWs and discussing the literature related to this association.